Tinjauan Karakteristik Sumber Daya dan Strategi Pengelolaan Ikan Semah Tor tambroides (Bleeker, 1852) - Mirna Dwirastina; Arif Wibowo (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2022)
Semah fish is a fish that has high economic value. The population of this fish has decreased drastically. Based on the studies that have been carried out, the problem of decreasing the population of Semah Fish raises management efforts that can ensure the sustainability of fish resources. The method used is direct observation in the field, fisherman's catch, and fish identification is carried out in molecular or DNA sequences. This review was conducted in 2022 on research that has been carried out in Sungai Manna, South Bengkulu Regency, and in Batang Tarusan, Pesisir Selatan Regency in 2012. The aim is to review and review the results of research that has been carried out related to the characteristics of fish management strategies and Semah Fish. . The results of the review on the study showed that the Semah Fish that lived in the Semangka River (Lampung Province), Manna River (Bengkulu Province), and Batang Tarusan River (West Sumatra Province) were identified as Tor tambroides species and constituted an integrated population or reproductive unit in this area. each of these rivers. In addition, it was found that several management efforts were carried out to maintain fish habitat, recommending that the Semah Fish conservation area in the Manna River can be determined, especially the Negara Kaya – Timun Island, the limitations of the size of fish that can be caught, which is more than 245 mm standard for the Manna River. , is greater than 206.6 mm for Batang Tarusan River, and regulates the fishing season in April and September.